2021
DOI: 10.3390/su131910863
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Challenges in the Value Chain of the Anadara tuberculosa Bivalve Mollusk in Ecuador

Abstract: The bivalve mollusk, Anadara tuberculosa (Black Shell, in Spanish Concha Prieta), is found on America’s Pacific coast, where it is harvested for subsistence and commercial markets. This paper aims to diagnose the performance of the black shell’s value chain. We also identify several challenges that must be addressed to improve the sustainability of the black shell fishery in Ecuador. The applied methodology was quantitative and descriptive. Its design was non-experimental, field, cross-sectional and ex post fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Additionally, research in capture fisheries has shown that utilizing rights-based management encourages fishers across low-and middle-income countries to fish more sustainably because they reap economic benefits, and in the long term, this benefits the broader community (Asche et al, 2018). In Ecuador, a study found that fishery workers engaged in bivalve farming petitioned for sustainability challenges to be addressed, including restoration, and strengthening of custody of mangrove ecosystems, improved sanitation and purification, and institutional investments (Prado-Carpio et al, 2021).…”
Section: Sustainabilitymentioning
confidence: 99%
“…Additionally, research in capture fisheries has shown that utilizing rights-based management encourages fishers across low-and middle-income countries to fish more sustainably because they reap economic benefits, and in the long term, this benefits the broader community (Asche et al, 2018). In Ecuador, a study found that fishery workers engaged in bivalve farming petitioned for sustainability challenges to be addressed, including restoration, and strengthening of custody of mangrove ecosystems, improved sanitation and purification, and institutional investments (Prado-Carpio et al, 2021).…”
Section: Sustainabilitymentioning
confidence: 99%